2020
DOI: 10.1186/s41824-020-00090-y
|View full text |Cite
|
Sign up to set email alerts
|

Texture indices of 4′-[methyl-11C]-thiothymidine uptake predict p16 status in patients with newly diagnosed oropharyngeal squamous cell carcinoma: comparison with 18F-FDG uptake

Abstract: Background In oropharyngeal squamous cell carcinoma (OPSCC), human papillomavirus (HPV)/p16 status is important as a prognostic biomarker. Purpose We evaluated the relationship between 4′-[methyl-11C]-thiothymidine (11C-4DST) and 18F-FDG PET texture indices and p16 status in patients with newly diagnosed OPSCC. Methods We retrospectively reviewed the collected data of 256 consecutive, previously untreated patients with primary head and neck tumors enrolled between November 2011 and October 2019. Complete d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this study, the accumulation of primary and metastatic lymph nodes were combined to calculate each PET parameter using the methodology of Ito et al [12] Many previous reports using [ 11 C]4DST/[ 18 F]FDG and [ 18 F]FDG have calculated PET parameters based on the primary tumor alone [6,11,[13][14][15]. However, as the presence or absence of regional lymph node metastasis is considered to have an impact on RFS, the findings of the present study, in which the aggregation of all lesions with similar biological characteristics was analyzed, are useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the accumulation of primary and metastatic lymph nodes were combined to calculate each PET parameter using the methodology of Ito et al [12] Many previous reports using [ 11 C]4DST/[ 18 F]FDG and [ 18 F]FDG have calculated PET parameters based on the primary tumor alone [6,11,[13][14][15]. However, as the presence or absence of regional lymph node metastasis is considered to have an impact on RFS, the findings of the present study, in which the aggregation of all lesions with similar biological characteristics was analyzed, are useful.…”
Section: Discussionmentioning
confidence: 99%
“…Ihara-Nishishita et al . [14] reported the relationship between texture indices of [ 11 C]4DST PET and [ 18 F]FDG PET in oropharyngeal squamous cell carcinoma. They concluded that texture indices of the primary lesion on [ 11 C]4DST PET may have predictive value for p16 status for targeted patients.…”
Section: Discussionmentioning
confidence: 99%
“…C]4DST/[ 18 F]FDG and [ 18 F]FDG have calculated PET parameters based on the primary tumor alone[6][11][13][14]…”
mentioning
confidence: 99%